Methylation of CpG island of p14(ARK), p15(INK4b) and p16(INK4a) genes in coke oven workers. (February 2015) - Zhang, H; Li, X; Ge, L; Yang, J; Sun, J; Niu, Q
To detect the blood genomic DNA methylation in coke oven workers and find a possible early screening index for occupational lung cancer, 74 coke oven workers as the exposed group and 47 water pump workers as the controls were surveyed, and urine samples and peripheral blood mononuclear cells (PBMCs) were collected. Airborne benzo[a]pyrene (B[a]P) levels in workplace and urinary 1-hydroxypyrene (1-OH-Py) levels were determined by high-performance liquid chromatography. DNA damage of PBMCs and the p14(ARK), p15(INK4b) and p16(INK4a) gene CpG island methylation in the promoter region were detected by comet assay and methylation-specific polymerase chain reaction techniques, respectively. Results show that compared with the controls, concentration of airborne B[a]Ps was elevated in the coke plant, and urinary 1-OH-Py's level and DNA olive tail moment in comet assay were significantly increased in the coke oven workers, and p14(ARK), p15(INK4b) and p16(INK4a) gene methylation rates were also significantly increased. With the working years and urinary 1-OH-Py's level, the rates of p14(ARK) and p16(INK4a) gene methylation were significantly increased while that of p15(INK4b) gene methylation displayed no statistical change. We conclude that PBMCs' p14(ARK) and p16(INK4a) gene methylation may be used for screening and warning lung cancer in coke oven workers.